Genotypic differences off storage proteins in four Scandinavian spring wheat cultivars during seed development - Peltonen, Jari; Sontag-Strohm, Tuula (Agricultural Research Centre of Finland, 1992)
Neljän sadonmuodostukseltaan ja leivontalaadultaan vaihtelevan kevätvehnän (Heta, Ruso, Reno, Kadett) satokomponentit, suurimolekyyliset gluteniinialayksiköt, gliadiinit sekä varastoproteiinien suhteelliset osuudet jyvän täyttymisjaksolla tutkittiin kenttäkokein kasvukausina 1989-90. Kokeet järjestettiin Helsingin yliopiston kasvintuotantotieteen laitoksella ja Hankkijan kasvinjalostuslaitoksella. Tulokset osoittivat, että aikaisuus on tärkeä valintakriteeri kevätvehnän korkean leivontalaadun kannalta. Lyhyt jyvän täyttymisjakso on yhteydessä voimakkaaseen suurimolekyylisten gluteniinien varastoitumiseen jyvän täyttymisjakson keskivaiheilla, mikä johti korkeaan valkuaispitoisuuteen ja valkuaisen laatuun mutta alhaiseen sadon määrään. Tulokset viittaavat siihen, että kevätvehnän sadon ja valkuaispitoisuuden välistä negatiivista suhdetta tulisi pyrkiä murtamaan valitsemalla aikaisin tuleentuvia, korkean jyvän valkuaispitoisuuden, korkean suurimolekyylisten gluteniinien määrän ja suuren jyvälukumäärän tähkään tuottavia vehnälinjoja.

Wheat (Triticum aestivum L.) is grown under a wide range of climatic conditions. Therefore, it is necessary to understand the underlying physiological phenomena which affect the quality of grain yield. The aim of this project was to study the interactions between cultivars in their accumulation and relative concentrations of the different protein groups of storage proteins at various stages of wheat grain development. Yield components, protein quantity and the quality of flour were examined. The study was carried out at the University of Helsinki, Department of Plant Production during 1989-1990. The cultivars used were Heta, Ruso, Reno and Kadett. In northern latitudes the early maturity class of a genotype is an important selection criterion associated with good breadmaking quality. The short grain filling period leads to a high rate of accumulation of high molecular weight glutenins, because it coincides with a rapid expansion of the endosperm in the middle of grain filling. The associated yield loss in these cultivars may be compensated by higher number of grains per ear. Therefore, selection of productive wheat Iines with early maturity, high protein concentration and high relative amount of high molecular weight glutenins, and high grain number per ear instead of high kernel weight may lead to more stable yield and improved breadmaking quality.
Keywords: Ka; kevätvehnä; jyvä; valkuaisaineet; proteiinit; lajikkeet; wheat; Triticum aestivum L.; storage proteins; yield components; northern latitudes